Morphological, Biochemical And Molecular Characterization Of Xanthomonas Citri Sub Sp. Citri Isolates From Different Agroclimatic Zones Of Maharashtra (Journal of Plant Disease Sciences, 2020)
Citrus is one of the important tropical and subtropical fruits in the world as well as in India which belongs to the family Rutaceaeand sub-family Aurantioedae. Among all factors responsible for decline in citrus production, citrus canker is one of the most serious problem which is caused by Xanthomonas citrisubsp. citri. Xanthomonas citri sub sp. citri was successfully isolated on the nutrient agar medium, from the fresh lesions on the leaves of naturally canker infected acid lime leaves collected from different agroclimatic zones of Maharashtra. The fourteen isolates were designated from Xcc-1 to Xcc-14 representing the agroclimatic zone. The studies on physiological characteristics of Xanthomonas citri sub sp. citri. showed the maximum growth of pathogen observe at temperature 300C and at pH level 7. All isolates of bacteria were found negative test for gram’s staining while positive for starch hydrolysis, potassium hydroxide test, catalase test, hydrogen sulphide production, gelatin liquefaction, acid and gas, indole production and nitrate reduction.The genetic variability was studied by using five ISSR and RAPD primers. Among ISSR primers Isolate Xcc-11 (Nagpur) had higher value of similarity coefficient (0.85) with Xcc-10 (Wardha), whereas Xcc-12 (Gadchiroli), had lower value of similarity coefficient (0.42) with Xcc-1 (Sindhudurg). The result of RAPD primers reveal that Isolate Xcc-11 (Nagpur) had higher value of similarity coefficient (0.81) with Xcc-10 (Wardha), whereas Xcc-2 (Dapoli), had lower value of similarity coefficient (0.41) with Xcc-13 (Gondia).
Keywords: Acide lime; Canker; Molecular marker; Variability